Institutional Weaknesses of Ukraine’s National Innovation System and their Consequences for the Country’s International Competitiveness (Economic and Political Thought, 2019)
The aim of the article is to identify the main institutional weaknessesof Ukraine’s National Innovation System and to try to determine theirconsequences for the competitiveness of the Ukrainian economy in terms ofinternational trade in high-technology and medium-high-technology goods,i.e. those created in industries based on knowledge and modern technologies.In other words, to examine whether and how Ukraine’s competitivenessin trade in these goods is changing in the face of the existing institutionalweaknesses of its National Innovation System. In order to analyse the countrycompetitiveness in international trade, B. Balassa’s method of analysingrevealed comparative advantages was applied.The in-depth analysis of the dynamics of the revealed comparativeadvantages in Ukrainian exports in the years 2001–2016 clearly shows thatthe Ukrainian economy not only did not have any long-term comparativeadvantages in trade in high-technology and medium-high-technology goodsin this period, but also its competitive position deteriorated in this respect.This should be attributed to strong institutional weaknesses within Ukraine’sNational Innovation System, which significantly lower the effectiveness of thissystem and also reduce the ability to create and commercialise knowledgeand innovation, as reflected in the lack of competitiveness of its economy intrade in high-technology goods.
Keywords: Ukraine, National Innovation System, institutions, international competitiveness